Mineral content, Antioxidant, and Antimicrobial analyses of Bee pollen Collected from Nilgiri Biosphere Nature Park, Coimbatore - Ramakrishnan, Yamuna (ENTOMOLOGIA HELLENICA, 2025)
Bee pollen is rich in phytochemicals exhibiting possible antimicrobial and antioxidant properties. This study evaluated the mineral content, antioxidant activity, and antimicrobial efficacy of bee pollen collected from hives, identified through palynological analysis, from different plant sources in the Nilgiri Biosphere Nature Park, Coimbatore. The DPPH method showed significant antioxidant potential, with the lowest IC50 value recorded in Eucalyptus fibrosa pollen (0.085 mg/ml). Antimicrobial tests revealed strong inhibition against Escherichia coli, Staphylococcus aureus, and Candida albicans, highlighting bee pollen’s potential as a natural bioactive agent.